Effect of Vitamin D on Urinary Albumin Excretion in Diabetic Nephropathy Patients: A Meta-analysis of Randomized Controlled Trials (Iranian Journal of Kidney Diseases, 2022)
It remains controversial, whether vitamin D reduces urinary albumin excretion in patients with diabetic nephropathy (DN). This metaanalysis was designed to evaluate the therapeutic effect of vitamin D, on urinary albumin excretion, in DN patients. Electronic databases, including PubMed, Embase, Web of Science, and Cochrane library were searched for randomized controlled trials (RCTs), regarding the effect of vitamin D on urinary albumin excretion in DN patients. The study selection and data extraction were conducted by two reviewers independently, and statistical analysis was performed using RevMan software, version 5.2. A total of nine RCTs including 1547 subjects were qualified. There were 815 participants in the study group and 732 in the control group. The fixed-effect model was used to analyze urinary albumin creatinine ratio (UACR) and urinary albumin excretion ratio (UAER), and the pooled standard mean difference (SMD) was -0.24 (95% CI: -0.39 to -0.09), P = .002, and -0.57 (95% CI: -0.71 to -0.43), P < .00001; respectively. These findings indicated that vitamin D-treated patients had a statistically significant reduction in UACR and UAER. High-quality RCTs are still required.  DOI: 10.52547/ijkd.7107